Experimental and numerical studies on a single-layer cylindrical reticulated shell with semi-rigid joints. (January 2015) - Ma, Huihuan; Fan, Feng; Wen, Peng; Zhang, Hao; Shen, Shizhao
Abstract: Most existing studies on single-layer spatial structures with semi-rigid joints were focused on spherical domes. The present paper analyzed the squared plan-form single-layer structures, examining the influence of joint-rigidity on the mechanical performances of the structures. An experiment has been conducted on a 5×6 m single-layer cylindrical reticulated shell with semi-rigid bolt-ball joints. The mechanical performance of the latticed shell is investigated in detail. Finite element analysis (FEA) model of the latticed shell is established taking material and geometric nonlinearities into account. The results show that the behavior determined using the FEA models correlates well with the experimentally observed behavior for the single-layer structures with semi-rigid joints. Highlights: Numerical and theoretical analyses of semi-rigid joints are carried out. Bending–rotation relationships of the joints are obtained. The FEA models can effectively describe the mechanical performance of the joints. A further parametric study is carried out on the socket joints. The mathematical model can effectively predict the bending–rotation curves of joints.